A low-temperature n-propanol gas sensor based on TeO2 nanowires as the sensing layer. Issue 37 (25th March 2015) - Shen, Yanbai; Fan, Anfeng; Wei, Dezhou; Gao, Shuling; Liu, Wengang; Han, Cong; Cui, Baoyu
Abstract : TeO2 nanowires with high surface-to-volume ratio and large mass production were synthesized by thermal evaporation method and showed a reversible response and quick response–recovery speed to n -propanol gas at low operating temperatures. Abstract : TeO2 nanowires were synthesized on Au-coated glass substrates using a thermal evaporation method. Structural characterization showed that TeO2 nanowires with high surface-to-volume ratio and large mass production had a single-crystal tetragonal structure. A gas sensor based on TeO2 nanowires showed a quick response–recovery speed and a reversible response to n -propanol gas at low operating temperatures.